Sustainability, Wellbeing and the Posthuman Turn - Smith, Thomas S. J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book examines how the way we conceive of, or measure, the environment changes the way we interact with it. Thomas Smith posits that environmentalism and sustainable development have become increasingly post-political, characterised by abstraction, and quantification to an unprecedented extent. As such, the book argues that our ways of measuring both the environment, such as through sustainability metrics like footprints and Payments for Ecosystem Services, and society, through gross domestic product and wellbeing measures, play a constitutive and problematic role in how we conceive of ourselves in the world. Subsequently, as the quantified environmental approach drives a dualistic wedge between the human and non-human realms, in its final section the book puts forward recent developments in new materialism and feminist ethics of care as providing practical ways of re-founding sustainable development in a way that firmly acknowledges human-ecological relations. This book will be an invaluable reference for scholars and students in the fields of human geography, political ecology, and environmental sociology.
Chapter 1 - The New Sustainable Development Agenda: An Introduction to Measurement and Conceptualisation -- Chapter 2 - The Abstraction of Nature and the Death of Environmental Politics: Our Calculable Earth -- Chapter 3 - Our Calculable Selves: The rise and hegemony of wellbeing discourse -- Chapter 4 - Ecological Ethics of Care and the Multiple Self: Revisiting the roots of environmentalism.
Keywords: Environment; Human geography; Physical geography; Economic development; Environmental Sciences; Human Geography; Physical Geography; Development Studies